Biochemical Studies On The Effect Of Aged Garlic Extract On Acetaminophen Induced Hepatotoxicity In Rats - Srikanth, M.; Sathyanarayana, M.L.; Chandrashekhara, N.; Manjunath , K.P. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Aged garlic extract has been shown to protect rats against acetaminophen induced liver injury through its antioxidant property. Aged garlic extract was given orally to rats for a period of 28 days. Liver damage was induced by inoculating acetaminophen at 500 mg/kg on 12th day of the experimental study. In acetaminophen treated rats there was significant increase in serum amino transferases (ALT and AST), but these enzymes were in the normal range in aged garlic extract (AGE) treated group indicating the protective effect of aged garlic extract against acetaminophen induced injury.